Ceramic fiber-based thermal insulation material, method for producing same, and use thereof
Patent Information
- Application Number
- CN202611404603.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]综上,现有陶瓷纤维基隔热材料面临着共性难题,涂层与柔性陶瓷纤维基体存在显著模量失配,难以协同变形
[0030]1、本发明的陶瓷纤维基隔热材料包括:陶瓷纤维基体、莫来石晶须界面层和高发射率涂层,外部的高发射率涂层快速将热量辐射出去,而中间层的莫来石晶须界面层通过微米级多孔网络结构形成多重反射界面,配合莫来石晶须本身对红外波段的高反射特性,有效抑制固相热传导并增强红外反射能力,使表面反射路径增加、辐射散热效率提升,从而构建高热阻屏障,高效阻隔残余热量向陶瓷纤维基体传递。基于该结构使其具有协同防隔热机制,通过外辐射内隔热的一体化设计,协同提升了陶瓷纤维基隔热材料的整体隔热与散热性能。
Smart Images

Figure CN122899050A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-temperature thermal protection materials technology, specifically relating to a ceramic fiber-based thermal insulation material, its preparation method, and its application. Background Technology
[0002] When aircraft fly at high speeds through the atmosphere, they face severe aerodynamic heating problems. Effective thermal protection design is necessary to prevent heat transfer inwards. Thermal protection systems are crucial for ensuring the safe operation of aircraft in extreme environments, and improving the overall performance of existing thermal protection systems is of great significance.
[0003] Flexible thermal insulation integrated materials are a key component of thermal protection systems. Their outermost layer is usually a flexible ceramic fiber matrix, such as ceramic fiber-based flexible felt, which is used to wrap and protect the internal thermal insulation structure and build the first line of defense against thermal shock. By introducing a thermal protection coating on the flexible ceramic fiber matrix, a flexible thermal insulation integrated design is realized. For example, “Mengxia L, Tao X, Yingna Z, et al. Composite thermal protection coating on woven silica fiber fabrics[J]. Science in China: Technological Science (English Edition), 2014(6):6.DOI:10.1007 / s11431-014-5546-9.” discloses a composite coating with an inner and outer layer structure. The outer layer relies on a mullite fiber / whisker skeleton to suppress surface cracking of the coating; the inner layer adds silica hollow spheres to achieve interface bonding control of the coating fabric. However, the tensile strength is significantly reduced after the introduction of the composite coating, and it does not have high infrared emission characteristics. The thermal protection capability relies only on the thermal insulation effect of the material itself, and the protection effect is limited under the strong aerodynamic heating conditions of high-speed aircraft.
[0004] Currently, extensive research has been conducted both domestically and internationally on forming high-emissivity coatings on the surface of ceramic fiber-based flexible felts, and multiple generations of products have been developed. The United States has successively developed a series of coatings such as DC92, C-9, and PCC. By composite high-emissivity ceramic particles such as SiC and SiB6 on the surface of AFRSI (Advanced Flexible Reusable Surface Insulation), the emissivity of the coating has been improved from 0.5 to 0.9 (Kim HS, Kang BR, Choi S M. Microstructure and mechanical properties of vacuum plasma sprayed HfC, TiC, and HfC / TiC ultra-high-temperature ceramic coatings[J]. Materials,2020, 13(1): 124.). Although it has a high emissivity, the stability of the coating and its thermal compatibility with the flexible ceramic fiber matrix still need to be optimized under long-term high-temperature oxidation conditions.Domestic research has also made some progress. For example, the paper “Zhang G, Xue Y, Liu P, et al. High emissivity double-layer coating on the flexible aluminum silicate fiber fabric with enhanced interfacial bonding strength and high temperature resistance[J]. Journal of the European CeramicSociety, 2021, 41(2): 1452-1458.” disclosed that a double-layer coating was prepared on the surface of aluminum silicate fiber fabric using SiC and ZrO2 as emissives, with an emissivity of 0.88. However, due to the problem of modulus mismatch between the rigid coating and the flexible ceramic fiber matrix, the coating is prone to peeling off. “Gao Q, Yan L, Mu Y, et al. TaSi2-SiC high-emissivity coating modified by SiB6 on flexible alumina fibre fabric with enhanced oxidation resistance and high interfacial bonding strength[J].Ceramics International, 2023, 49(8): 12643-12652.” "A modified high emissivity coating was prepared on the surface of alumina fiber cloth by introducing SiB6 and Si powder, but the added SiB6 seriously impaired the flexibility of the fiber cloth."
[0005] In summary, existing ceramic fiber-based thermal insulation materials face a common challenge: a significant modulus mismatch exists between the coating and the flexible ceramic fiber matrix, making coordinated deformation difficult. Although the concept of integrated thermal insulation has been proposed, a flexible integrated thermal insulation material that can provide significant thermal insulation, achieve good bonding between the flexible ceramic fiber matrix and the high-emissivity coating, and maintain flexibility is still lacking. Therefore, developing a novel integrated thermal insulation coating that combines high heat dissipation efficiency, excellent thermal insulation performance, and flexible self-adaptive capabilities is a technical challenge that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing ceramic fiber-based thermal insulation materials.
[0007] Another object of the present invention is to provide a ceramic fiber-based thermal insulation material obtained by the above preparation method. The ceramic fiber-based thermal insulation material includes: a ceramic fiber matrix, a mullite whisker interface layer and a high emissivity coating arranged sequentially from bottom to top. The mullite whisker interface layer is grown in situ on the surface of the ceramic fiber matrix. The high emissivity coating includes: silicon carbide.
[0008] Another object of the present invention is to provide the application of the above-mentioned ceramic fiber-based thermal insulation material as a thermal protection material.
[0009] The objective of this invention is achieved through the following technical solution.
[0010] A method for preparing a ceramic fiber-based thermal insulation material includes the following steps:
[0011] Step 1: Coat the first slurry onto the surface of the ceramic fiber matrix, dry it, heat-treat it at 800~1200℃ for 1~4 hours in an air environment, and cool it to room temperature to obtain a mullite whisker interface layer on the ceramic fiber matrix. The method for preparing the first slurry includes: mixing aluminum trifluoride (powder), silica sol and a first solvent until uniform to obtain the first slurry. The ratio of aluminum in aluminum trifluoride to silicon in silica sol is (1~2):1 by molar ratio, and the thickness of the mullite whisker interface layer is 1000~1800nm.
[0012] In step 1, the ceramic fiber matrix is ceramic fiber cloth.
[0013] In step 1, the first solvent is anhydrous ethanol.
[0014] In step 1, the silica sol comprises silica and water, and the solid content of the silica sol is 20~40wt%.
[0015] In step 1, the solid content of the first slurry is 5~50wt%.
[0016] In step 1, the drying temperature is 30~50℃ and the drying time is 10~24 hours.
[0017] Step 2: Coat the surface of the mullite whisker interface layer with the second slurry and dry it to obtain a high emissivity coating on the mullite whisker interface layer, thereby obtaining a ceramic fiber-based thermal insulation material. The method for preparing the second slurry includes: mixing silicon carbide (powder), aluminum-silicon composite sol, polyvinyl alcohol aqueous solution and a second solvent until uniform to obtain the second slurry. The ratio of silicon carbide, aluminum-silicon composite sol, polyvinyl alcohol aqueous solution and the second solvent by mass parts is (4~6):(4~6):(0.5~1.5):(2~4).
[0018] In step 2, the thickness of the high emissivity coating is 1~40 μm (preferably 5~15 μm).
[0019] In step 2, the polyvinyl alcohol content in the polyvinyl alcohol aqueous solution is 5~20 wt%.
[0020] In step 2, the second solvent is water.
[0021] In step 2, the method for preparing the aluminum-silicon composite sol includes: mixing aluminum sol, silica sol and a third solvent until homogeneous to obtain the aluminum-silicon composite sol, wherein the ratio of aluminum sol, silica sol and the third solvent by mass is (2~6):(2~6):1.
[0022] In the method for preparing aluminum-silicon composite sol, the third solvent is water.
[0023] In the method for preparing aluminum-silicon composite sol, the aluminum sol includes boehmite (γ-AlOOH) and water, and the solid content of the aluminum sol is 10~30 wt%.
[0024] In the method for preparing aluminum-silicon composite sol, the silica sol includes silica and water, and the solid content of the silica sol is 20~40 wt%.
[0025] In step 2, the drying temperature is 30~50℃ and the drying time is 10~24 hours.
[0026] In steps 1 and 2, the coating method is spraying.
[0027] The ceramic fiber-based thermal insulation material obtained by the above preparation method.
[0028] The above-mentioned ceramic fiber-based thermal insulation materials are used as thermal protection materials.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0030] 1. The ceramic fiber-based thermal insulation material of the present invention comprises: a ceramic fiber matrix, a mullite whisker interface layer, and a high emissivity coating. The outer high emissivity coating rapidly radiates heat away, while the middle mullite whisker interface layer forms multiple reflective interfaces through a micron-level porous network structure. Combined with the high reflectivity of mullite whiskers in the infrared band, it effectively suppresses solid-phase heat conduction and enhances infrared reflection capability, increasing the surface reflection path and improving radiation heat dissipation efficiency. This constructs a high thermal resistance barrier, effectively blocking residual heat from being transferred to the ceramic fiber matrix. Based on this structure, it possesses a synergistic heat insulation mechanism. Through the integrated design of external radiation and internal heat insulation, the overall thermal insulation and heat dissipation performance of the ceramic fiber-based thermal insulation material is synergistically improved.
[0031] 2. This invention constructs a mullite whisker interface layer between a rigid, high-emissivity coating and a flexible ceramic fiber matrix. Through a point-to-point discontinuous connection between the mullite whiskers and the ceramic fiber matrix, the rigid silicon carbide material is freed from its own rigidity in the axial direction, achieving adaptive flexible deformation with the ceramic fiber matrix. This strategy overcomes the common problem of interface mismatch between rigid coatings and flexible substrates.
[0032] 3. The preparation process of this invention is highly controllable. Aluminum trifluoride provides an aluminum source for the formation of mullite whiskers under high-temperature oxidation conditions. On the other hand, it can induce the reaction between the alumina contained in the ceramic fiber matrix and the silicon oxide in the silica sol to generate mullite whiskers. Therefore, by controlling the solid content of the first slurry and the molar ratio of aluminum in aluminum trifluoride and silicon in silica sol, the morphology, thickness and density of mullite whiskers can be precisely controlled, thereby optimizing the internal pore structure of the ceramic fiber-based thermal insulation material and effectively controlling the heat conduction path, thus optimizing the comprehensive performance of the ceramic fiber-based thermal insulation material. Attached Figure Description
[0033] Figure 1 SEM image of the mullite whisker interface layer obtained in step 1 of Example 1;
[0034] Figure 2 SEM image of the surface containing the high emissivity coating of the ceramic fiber-based thermal insulation material prepared in Example 1;
[0035] Figure 3 The tensile strength of the ceramic fiber-based thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2;
[0036] Figure 4 The interfacial bonding strength of the ceramic fiber-based thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2;
[0037] Figure 5 The images show the actual physical images of the ceramic fiber-based thermal insulation materials prepared in Examples 1, 1, and 3 after bending and folding tests. Specifically, (a) is an actual physical image of the ceramic fiber-based thermal insulation material prepared in Example 1 after bending, (b) is an actual physical image of the ceramic fiber-based thermal insulation material prepared in Comparative Example 1 after bending, (c) is an actual physical image of the ceramic fiber-based thermal insulation material prepared in Example 1 after folding 30 times, (d) is an actual physical image of the ceramic fiber-based thermal insulation material prepared in Comparative Example 1 after folding 30 times, (e) is an actual physical image of the ceramic fiber-based thermal insulation material prepared in Comparative Example 3 after bending, and (f) is an actual physical image of the ceramic fiber-based thermal insulation material prepared in Comparative Example 3 after folding 30 times.
[0038] Figure 6The average emissivity of the ceramic fiber-based thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2 is given by the ceramic fiber matrix. Detailed Implementation
[0039] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0040] The purity and manufacturers of the pharmaceuticals involved in the following examples and comparative examples are as follows:
[0041] Table 1
[0042]
[0043] Ceramic fiber cloth (main phase is aluminum-silicon composite phase (Al2O3·SiO2), the content of aluminum-silicon composite phase is greater than 95%): purchased from Hubei Feilihua Quartz Glass Co., Ltd.
[0044] The silica sol comprises silica and water, with a solid content of 40 wt%. It was purchased from Guangdong Huierte Nanotechnology Co., Ltd.
[0045] The aluminum sol comprises boehmite (γ-AlOOH) and water, with a solid content of 20 wt%. It was purchased from Hangzhou Hengge Nanotechnology Co., Ltd.
[0046] In the following embodiments, the vertical distance between the spray gun nozzle and the substrate is 10 cm, and the spray gun moving speed is 3 cm / s. -1 The substrate is a ceramic fiber matrix, a mullite whisker interface layer, or a high emissivity coating.
[0047] In the following examples, the water is deionized water.
[0048] Examples 1-3
[0049] A method for preparing a ceramic fiber-based thermal insulation material includes the following steps:
[0050] Step 1: Using a high-pressure electric spray gun (Ningbo Huipu Hardware Tools Co., Ltd., SG9620), the first slurry is sprayed onto the surface of the ceramic fiber matrix (ceramic fiber cloth). It is dried at 40℃ for 12 hours, then placed in a high-temperature sintering furnace. In an air environment, the temperature is increased to 1000℃ at a rate of 5℃ / min and heat-treated at 1000℃ for 2 hours. After cooling to room temperature, a mullite whisker interface layer (urchin-like structure heat-insulating coating) is obtained on the ceramic fiber matrix. The method for preparing the first slurry includes: placing powdered aluminum trifluoride in a planetary ball mill at 300 r·min... -1The ball was milled at a rotation speed of 3 hours (by mass, the ratio of grinding balls to powdered aluminum trifluoride was 1:1). Then, the milled aluminum trifluoride, silica sol, and the first solvent (anhydrous ethanol) were mixed until uniform to obtain a first slurry with a solid content of 10 wt%. By mass, the ratio of aluminum in aluminum trifluoride to silicon in silica sol was X.
[0051] Step 2: The second slurry is sprayed onto the surface of the mullite whisker interface layer using a high-pressure electric spray gun and dried at 40°C for 12 hours to obtain a high emissivity coating on the mullite whisker interface layer, thus obtaining a ceramic fiber-based thermal insulation material. The method for preparing the second slurry includes: placing powdered silicon carbide in a planetary ball mill and ball milling it at a rotation speed of 300 r / min for 4 hours (by mass, the ratio of grinding balls to powdered silicon carbide in Step 2 is 1:1). The ball-milled silicon carbide, aluminum-silicon composite sol, polyvinyl alcohol aqueous solution, and the second solvent (water) are mixed until homogeneous to obtain the second slurry. By mass, the ratio of silicon carbide, aluminum-silicon composite sol, polyvinyl alcohol aqueous solution, and the second solvent is 5:5:1:3, and the polyvinyl alcohol content in the polyvinyl alcohol aqueous solution is 10%. The method for preparing aluminum-silicon composite sol by weight includes: mixing aluminum sol, silica sol and a third solvent (water) until homogeneous to obtain aluminum-silicon composite sol. The ratio of aluminum sol, silica sol and the third solvent in step 2 is 3.6:3:1 by mass.
[0052] The values of X are shown in Table 2.
[0053] Table 2
[0054]
[0055] In Examples 1-3, the mullite whisker interface layer, the high emissivity coating, and the ceramic fiber matrix have the same planar dimensions.
[0056] Comparative Example 1
[0057] A method for preparing a ceramic fiber-based thermal insulation material is basically the same as that in Example 1, except that the first slurry is different. The method for obtaining the first slurry in Comparative Example 1 includes mixing mullite whiskers and anhydrous ethanol to obtain a first slurry with a solid content of 10 wt%.
[0058] In Comparative Example 1, the mullite whisker interface layer was not generated in situ. The non-situ generated mullite whiskers had problems such as uneven distribution and poor interface bonding, and could not construct an effective reflection network.
[0059] Comparative Example 2
[0060] A method for preparing a ceramic fiber-based thermal insulation material includes: spraying a second slurry (the same as the second slurry in Example 1) onto the surface of a ceramic fiber matrix using a high-pressure electric spray gun, drying it at 40°C for 12 hours, obtaining a high emissivity coating on the ceramic fiber matrix, and obtaining the ceramic fiber-based thermal insulation material.
[0061] Comparative Example 3
[0062] A method for preparing a ceramic fiber-based thermal insulation material includes the following steps:
[0063] Step 1: The second slurry (the same as the second slurry in Example 1) is sprayed onto the surface of the ceramic fiber matrix (ceramic fiber cloth) using a high-pressure electric spray gun and dried at 40°C for 12 hours to obtain a high emissivity coating on the ceramic fiber matrix.
[0064] Step 2: The first slurry (the same as the first slurry in Example 1) is sprayed onto the surface of the high emissivity coating using a high-pressure electric spray gun, dried at 40°C for 12 hours, and then placed in a high-temperature sintering furnace. In an air environment, the temperature is raised to 1000°C at a rate of 5°C / min and heat-treated at 1000°C for 2 hours. After cooling to room temperature, a mullite whisker interface layer is obtained on the high emissivity coating, resulting in a ceramic fiber-based thermal insulation material.
[0065] In Examples 1-3 and Comparative Example 1, the thicknesses of the mullite whisker interface layer were 1373.92 nm, 1944.43 nm, 2419.16 nm, and 2536.09 nm, respectively, and the loading of mullite whiskers on the ceramic fiber matrix was 442.91 g·m³, respectively. -2 441.77 g·m -2 433.25 g·m -2 442.43 g·m -2 In Examples 1-3 and Comparative Examples 1-2, the thicknesses of the high emissivity coatings were 9.62 μm, 10.38 μm, 9.75 μm, 10.21 μm, and 9.84 μm, respectively.
[0066] The microstructure of the mullite whisker interface layer obtained in step 1 of Example 1 is as follows: Figure 1 As shown, by Figure 1 It is known that the mullite whisker interface layer exhibits an ideal sea urchin-like structure. The ceramic fiber matrix is covered by mullite whiskers. The mullite whiskers use the ceramic fiber matrix as the growth base point and are arranged in a radial interlacing pattern to form a three-dimensional skeleton similar to a sea urchin. Adjacent mullite whiskers share the same initial growth point to form radial crystal clusters. The mullite whiskers between adjacent crystal clusters overlap and gradually form a multi-level open pore structure on the surface of the ceramic fiber matrix, which in turn forms a micron-level porous network structure.
[0067] The microstructure of the surface containing the high emissivity coating of the ceramic fiber-based thermal insulation material prepared in Example 1 is as follows: Figure 2 As shown. By Figure 2 It can be seen that the high emissivity coating is uniformly and continuously distributed, effectively masking the porous structure of the mullite whisker interface layer.
[0068] Tensile strength was tested on the samples at room temperature using an electronic universal testing machine. The test parameters included a preload force of 0.5 N and a tensile speed of 2 mm / min. The material used was one of the ceramic fiber-based thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2. The results are as follows: Figure 3 As shown. By Figure 3 It can be seen that the tensile strengths of the ceramic fiber-based thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2 are 72.01 MPa, 38.57 MPa, 58.43 MPa, 32.66 MPa, and 37.62 MPa, respectively. The tensile strength of the ceramic fiber matrix (which was heat-treated at 1000℃ for 2 hours in air before testing) and the ceramic fiber-based thermal insulation material prepared in Comparative Example 3 were tested using an electronic universal testing machine. The tensile strength of the ceramic fiber matrix was measured to be 32.48 MPa, and the tensile strength of the ceramic fiber-based thermal insulation material prepared in Comparative Example 3 was 28.63 MPa. It can be seen that the tensile strength of the ceramic fiber-based thermal insulation materials prepared in Examples 1-3 is improved to varying degrees compared with that of the ceramic fiber matrix. Among them, the ceramic fiber-based thermal insulation material prepared in Example 1 has the highest tensile strength. The high tensile strength can significantly improve its structural stability under harsh conditions such as high temperature and high load, and effectively resist deformation and fracture. Comparing Comparative Example 3 and Example 1, it can be seen that the spraying order of the first slurry and the second slurry directly determines the tensile strength. The interlayer bonding between the ceramic fiber matrix and the mullite whisker interface layer, as well as the interlayer bonding between the mullite whisker interface layer and the high emissivity coating, are the key factors affecting the tensile strength.
[0069] The interfacial bonding strength was tested using the vertical tensile method on an electronic universal testing machine. During the test, the material was cut to a length and width of 30 mm as a sample. The material was one of the ceramic fiber-based thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2. The bottom surface of the ceramic fiber matrix of the sample was fixed to an aluminum alloy mold using double-sided tape. The aluminum alloy mold was then fixed in the fixture of the electronic universal testing machine for interfacial bonding strength testing. The tensile strength was increased at a speed of 0.5 mm / min until the ceramic fiber matrix and coating separated (when the material was the ceramic fiber-based thermal insulation material prepared in Examples 1-3 and Comparative Example 1, the ceramic fiber matrix and mullite whisker interface layer separated (i.e., the coating was a mullite whisker interface at this time); when the material was the ceramic fiber-based thermal insulation material prepared in Comparative Example 2, the ceramic fiber matrix and high emissivity coating separated (i.e., the coating was a high emissivity coating at this time)). The tensile direction was perpendicular to the sample, and the preload force was 0.01 N. Five parallel samples were tested for each sample, and the average value was taken as the interfacial bonding strength. Test results are as follows Figure 4 As shown. By Figure 4 It can be seen that the interfacial bonding strengths of the ceramic fiber-based thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2 are 54.51 kPa, 53.79 kPa, 42.81 kPa, 40.58 kPa, and 38.17 kPa, respectively. The interfacial bonding strength of the ceramic fiber-based thermal insulation material prepared in Comparative Example 3, obtained using the same testing method, is 36.83 kPa.
[0070] Under the same bending action, the ceramic fiber-based thermal insulation material prepared in Example 1, and the ceramic fiber-based thermal insulation materials prepared in Comparative Examples 1 and 3 were bent, and the actual images are shown in the following figures. Figure 5 of (a) Figure 5 (b) and Figure 5 As shown in (e), by Figure 5 of (a) Figure 5 (b) and Figure 5 As can be seen from (e), the ceramic fiber-based thermal insulation material prepared in Comparative Example 3 has the worst flexibility. Compared with Comparative Example 1 and Comparative Example 3, the ceramic fiber-based thermal insulation material prepared in Example 1 has better flexibility. Its bending part is a continuous and smooth arc without a straight section in the middle, which makes it better able to adapt to complex curved surface structures, facilitates installation and construction, has a low risk of cracking, and can maintain structural integrity during long-term service.
[0071] The ceramic fiber-based thermal insulation materials prepared in Example 1, Comparative Example 1, and Comparative Example 3 were used as samples. The samples were subjected to a folding test using an MIT folding strength tester. The folding angle was 135°, the tension was 4.91 N, and the number of folds was 30. Calculations showed that after 30 folds, the mass loss rates of the ceramic fiber-based thermal insulation materials prepared in Example 1 and Comparative Example 1 were 0.3% and 3.7%, respectively. The appearance of the ceramic fiber-based thermal insulation material prepared in Example 1 after 30 folds is shown below. Figure 5 As shown in (c), the appearance of the ceramic fiber-based thermal insulation material prepared in Comparative Example 1 after 30 folds is as follows. Figure 5 As shown in (d), the appearance of the ceramic fiber-based thermal insulation material prepared in Comparative Example 3 after 30 folds is as follows. Figure 5 As shown in (f), by Figure 5 (c) Figure 5 (d) and Figure 5 As shown in (f), the high emissivity coating at the fold of the ceramic fiber-based thermal insulation materials prepared in Comparative Examples 1 and 3 showed significant peeling, especially in Comparative Example 3 (this is because the high emissivity coating is in direct contact with the flexible ceramic fiber matrix, and the two have different deformation capabilities, which easily leads to a decrease in interface bonding performance and adhesion stability; after heat treatment at 1000℃ for 2 hours, the high emissivity coating becomes brittle and its flexibility decreases). In contrast, the high emissivity coating at the fold of the ceramic fiber-based thermal insulation material prepared in Example 1 showed almost no peeling, proving that the ceramic fiber-based thermal insulation material prepared in Example 1 has excellent anti-folding durability and structural stability.
[0072] According to ASTM E307-72 (2019), the material was tested using an infrared spectroradiometer. The material was a ceramic fiber matrix. Figure 6 The method involves using one of the following ceramic fiber-based thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2: (1) the material is a ceramic fiber matrix; (2) an infrared radiometer irradiates the surface of the ceramic fiber matrix; (3) the material is the ceramic fiber-based thermal insulation material prepared in Examples 1-3 or Comparative Examples 1-2; and (4) the material is the high-emissivity coating surface irradiated by the infrared radiometer. The tests were conducted at room temperature in an atmospheric atmosphere (the spectral resolution of the infrared radiometer was 0.1 cm⁻¹ during the tests). -1 The emissivity of the material in the 2–14 μm band was obtained and averaged, as shown in the following results. Figure 6 As shown. By Figure 6 It can be seen that the average emissivity of the ceramic fiber-based thermal insulation materials prepared in Examples 1-3, the ceramic fiber-based thermal insulation materials prepared in Comparative Examples 1-2, and the ceramic fiber matrix in the 2-14 μm band are 0.858, 0.841, 0.837, 0.834, 0.832, and 0.794, respectively. Therefore, the ceramic fiber-based thermal insulation material of Example 1 can radiate heat away with the highest efficiency.
[0073] Ceramic fiber-based thermal insulation material was sewn onto the surface of a 5mm thick alumina flexible thermal insulation felt (NF-1600, Shanghai Rongrong New Material Technology Co., Ltd.) (the ceramic fiber matrix and the alumina flexible thermal insulation felt were in contact). A 1200℃ butane flame torch was used as the heat source to burn the surface containing the high emissivity coating (hot surface) for 300 seconds. The temperature of the surface containing the alumina flexible thermal insulation felt (cold surface) was measured using a handheld infrared thermal imager (model LT7-P, Zhejiang Dali Technology Co., Ltd.). The measured temperatures of the cold surfaces in Examples 1-3 and Comparative Examples 1-2 were 282℃, 335℃, 362℃, 348℃, and 359℃, respectively. The ceramic fiber-based thermal insulation material prepared in Example 1 showed good thermal insulation performance.
[0074] The variation in the whisker structure within the mullite whisker interface layer is the primary cause of changes in the tensile strength and interfacial bonding strength of ceramic fiber-based thermal insulation materials. In Example 1, the mullite whisker interface layer thickness is smaller (and the mullite whisker length is shorter), allowing the aluminosilicate composite sol to penetrate better along the gaps between the mullite whiskers during the second slurry application. This facilitates the bonding of the high-emissivity coating, the mullite whisker interface layer, and the ceramic fiber matrix. The adhesive effect of the aluminosilicate composite sol not only promotes interfacial bonding but also enhances the bundle cohesion of the fiber bundles (the internal structure of the ceramic fiber cloth contains fiber bundles), thereby improving tensile properties.
[0075] Compared with Comparative Example 1, Example 1 significantly improved mechanical strength and thermal insulation performance by growing a mullite whisker interface layer in situ on a ceramic fiber matrix as a thermal insulation layer. Compared with Comparative Example 2, the introduction of the mullite whisker interface layer significantly improved the interfacial bonding performance between the high emissivity coating and the ceramic fiber matrix, and buffered thermal stress mismatch through its unique radial crystal cluster structure, avoiding the failure of heat dissipation path due to coating peeling or crack propagation, thereby greatly improving the overall thermal insulation performance.
[0076] In summary, the urchin-like structure of the mullite whisker interface layer solves the modulus mismatch problem between the high-emissivity coating (rigid coating) and the ceramic fiber matrix (flexible matrix) through a point-to-point discontinuous connection method (mullite whiskers are discretely overlapped between the ceramic fiber matrix and the high-emissivity coating). This ensures excellent thermal insulation and radiative heat dissipation performance while endowing the coating with the flexibility to adapt to the deformation of the matrix. Furthermore, the in-situ generated mullite whiskers form a continuous, uniform whisker network with a multi-level porous structure, whereas off-site generated mullite whiskers suffer from uneven distribution and poor interfacial bonding, failing to construct an effective reflective network. This invention extends the thermal radiation path through a multiple scattering mechanism, increasing reflectivity and thus improving its heat dissipation efficiency and thermal insulation performance.
[0077] The present invention has been described above by way of example. It should be noted that any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort without departing from the core of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a ceramic fiber-based thermal insulation material, characterized in that, Includes the following steps: Step 1: Coat the surface of the ceramic fiber matrix with the first slurry, dry it, heat treat it at 800~1200℃ for 1~4 hours in an air environment, and cool it to room temperature to obtain a mullite whisker interface layer on the ceramic fiber matrix. The method for preparing the first slurry includes: mixing aluminum trifluoride, silica sol and a first solvent until uniform to obtain the first slurry. The first solvent is anhydrous ethanol. The ratio of aluminum in aluminum trifluoride to silicon in silica sol is (1~2):1 by molar ratio. The thickness of the mullite whisker interface layer is 1000~1800nm. Step 2: Coat the surface of the mullite whisker interface layer with the second slurry and dry it to obtain a high emissivity coating on the mullite whisker interface layer, thereby obtaining a ceramic fiber-based thermal insulation material. The method for preparing the second slurry includes: mixing silicon carbide, aluminum-silicon composite sol, polyvinyl alcohol aqueous solution and a second solvent until uniform to obtain the second slurry. By mass parts, the ratio of silicon carbide, aluminum-silicon composite sol, polyvinyl alcohol aqueous solution and the second solvent is (4~6):(4~6):(0.5~1.5):(2~4), and the second solvent is water.
2. The preparation method according to claim 1, characterized in that, In step 2, the thickness of the high emissivity coating is 1~40 μm.
3. The preparation method according to claim 1, characterized in that, In step 1, the solid content of the first slurry is 5~50wt%.
4. The preparation method according to claim 1, characterized in that, In step 1, the silica sol comprises silica and water, and the solid content of the silica sol is 20~40wt%.
5. The preparation method according to claim 1, characterized in that, In step 2, the method for preparing aluminum-silicon composite sol includes: mixing aluminum sol, silica sol and a third solvent until homogeneous to obtain aluminum-silicon composite sol. The ratio of aluminum sol, silica sol and the third solvent by mass is (2~6):(2~6):1, and the third solvent is water.
6. The preparation method according to claim 1, characterized in that, In step 1, the ceramic fiber matrix is ceramic fiber cloth.
7. The preparation method according to claim 5, characterized in that, In the method for preparing aluminum-silicon composite sol, the aluminum sol includes boehmite and water, and the solid content of the aluminum sol is 10~30 wt%.
8. The preparation method according to claim 5, characterized in that, In the method for preparing aluminum-silicon composite sol, the silica sol includes silica and water, and the solid content of the silica sol is 20~40 wt%.
9. The ceramic fiber-based thermal insulation material obtained by the preparation method according to any one of claims 1 to 8.
10. The application of the ceramic fiber-based thermal insulation material as described in claim 9 as a thermal protection material.